2002
DOI: 10.1046/j.1460-9592.2002.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex on Ventricular Arrhythmic Events in Patients with Congestive Heart Failure

Abstract: The propensity to develop specific arrhythmias varies between the sexes. Patients with congestive heart failure (CHF) have a high prevalence of ventricular ectopy. However, it is not known if sex related differences exist in the susceptibility to arrhythmias in the setting of CHF. The study population included 159 men and 77 women (mean age 61 +/- 14 years) admitted for decompensated CHF. The severity of atrial and ventricular arrhythmias was assessed by 24-hour Holter monitoring. None of the patients were on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The presence of non-ischaemic cardiomyopathy is associated with a lower overall mortality when compared to patients with ischaemic cardiomyopathy. 1 , 15 , 17 , 24 , 25 It can also not be ruled out that there is a bias in that physicians tend to withhold ICD-therapy from women with worse prognosis. An additional factor may be that women in general have a longer life expectancy than men.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of non-ischaemic cardiomyopathy is associated with a lower overall mortality when compared to patients with ischaemic cardiomyopathy. 1 , 15 , 17 , 24 , 25 It can also not be ruled out that there is a bias in that physicians tend to withhold ICD-therapy from women with worse prognosis. An additional factor may be that women in general have a longer life expectancy than men.…”
Section: Discussionmentioning
confidence: 99%
“…Saba et al (22) found that in female mice, estrogen prolongs atrioventricular nodal conduction and the right ventricular effective refractory period. In contrast, Aronson and Burger (23) found that complex ventricular ectopy and episodes of ventricular tachycardia are significantly lower in women. However, this was not a surgical series; therefore, patients were not exposed to all of the potential triggering factors that act exclusively as a consequence of surgery.…”
Section: Discussionmentioning
confidence: 85%
“…The underlying causes for the more favorable arrhythmic profile of women are not entirely clear but may be related to the lower propensity to sustained ventricular tachycardia in the nonischemic heart failure setting 15,16 but also for ischemic cardiomyopathy-associated sudden cardiac death. [17][18][19] In our sample, despite having more women with nonischemic cardiomyopathy, the overall reduction in arrhythmic burden was still present even after adjustment for baseline differences.…”
Section: Discussionmentioning
confidence: 99%